Failed endoscopic "over-the-scope" clip repair following iatrogenic colon perforation during screening colonoscopy. Issue 2 (2015) - Higham, Anna Kane; Lo, Winifred; Vanagunas, Arvydas; Crandall, Marie
No abstract available